Study of Service Quality Effect on Purchase Decision of Tamansari Cendekia Apartment Semarang - Leonard Wicak Utomo; Harry Soesanto (Budapest International Research and Critics University, 2022)
The increasing population growth in the city of Semarang makes the need for housing higher, while the lack of available land in urban areas makes developers create apartments as a solution for someone who wants a place to live closer to the city center. This has resulted in increasing competition between apartment developments, one of which is the Tamansari Cendekia Apartment Semarang. The number of apartments in the city of Semarang has made the sales of the Tamansari Cendekia Apartment units decline. The purpose of this study was to determine the effect of service quality on brand image, price, and purchase decisions. The population used is the consumer who bought the Tamansari Cendekia Apartment with a sample of 115 respondents, and the sampling technique used was purposive sampling. The method of data collection was done through a questionnaire. This research uses Structural Equation Modeling (SEM) analysis technique. The results of the analysis show that service quality has a positive and significant effect on brand image, price, and purchase decisions, and brand image and price have a positive and significant effect on purchase decisions.